Priority areas of strengthening the economic security of the food industry - Сокровольська, Наталія; Фень, Катерина; Скляр, Євгенія; Чикуркова, Алла; Наконечна, Катерина (INDEPENDENT JOURNAL OF MANAGEMENT & PRODUCTION(IJM&P), 2020)
The current operating conditions of enterprises are due to a high degree of instability, which is due to the situation affected by the global economic crisis. This leads to a general decrease in the level of economic security of enterprises and, as a consequence, the ability to ensure their sustainable development. Insufficient elaboration of the problem of overcoming the low level of economic security of food industry enterprises of Ukraine and the need to further disclose a number of issues to determine the components of the economic security system and the mechanism of its strengthening determined the purpose and objectives of research. The purpose of the research is to outline the priority areas for strengthening the economic security of the food industry of Ukraine. In accordance with the outlined goal, the following complex scientific tasks were set and solved: the conceptual bases of the mechanism of formation and strengthening of economic security of enterprises, which ensures the implementation of the innovative strategy of their development, were researched and substantiated; to make forecast calculations ofindicators of the level of economic security in the conditions of its strengthening for the investigated enterprises of the branch;an assessment of the impact of various factors influencing the formation of economic security of food industry enterprises of Ukraine; substantiated components of the economic security management system of food industry enterprises, the functioning of which is ensured by the implementation of a set of strategies, supplemented by a strategy of positive image formation and analysis of the initial position of the enterprise, development and implementation of corrective measures based on effective management
Keywords: Enterprise;Economic;Security;Food;Industry;Risks;Profitability;Image;Strategy